A study of abnormal semen parameters in infertile couples in Assam, India - Juneja, Parija; Phukan, Pranay K.; Changmai, Debojit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The importance of male factor contribution to infertility is well recognised. Semen analysis is an indispensable diagnostic tool in the evaluation of the male partners of infertile couples. Aim and objective of the study was conducted to determine the abnormalities in semen among male partners in infertile couples. Methods: Detailed history, examination and semen analysis was done. Semen samples were analysed for volume, viscosity, sperm concentration, motility, and morphology, according to WHO guidelines. Results: This study, done at a tertiary care center in north eastern India has demonstrated that abnormal semen quality is a major factor contributing to infertility in couples. Total number of participants were 94. Most of the male partners i.e. 65.96%, who came for infertility evaluation were between 30-39 years of age with 56.38% participants having abnormal semen parameters. The most common abnormality found was asthenozoospermia seen in 35.11% of cases followed by oligozoospermia seen in 25.53% of cases. Teratozoospermia and azoospermia were seen in 7.45% and 4.26% of cases respectively. Conclusions: Males contribute towards infertility in couples significantly. Abnormal semen pattern is a common cause. More research is needed to render more valuable and significant results regarding male infertility.